IMPROVING TECHNICAL TRAINING PERFORMANCE WITH KNOWLEDGE MANAGEMENT PRINCIPLES - Taufiqurokhman; Watriningsih; Sumarni, Lilik (Universitas prof. Dr. Moestopo (Beragama), 2023)
Programs (EDP) which main purpose is to accelerate learning process for fresh graduate new employees in the first five years of their career. Based on the survey result and the focus group discussion, there are two valid root causes of the problem, which are training planning process quality and training execution quality. The focus group discussion also resulted in business solutions to solve the problem by considering KM Metrics (Participation, Capture and Reuse) including: improve planning process and availability of training information by improving web-based information system, add more Guided Experience (GE) program and utilize IBU Subject Matter Expert (SME) to reduce dependency on overseas instructor as well as to encourage participation, capture and reuse of information within business unit, and using technology for implementing long distance learning (tele-conference training, etc).